The Classification of Frobenius Q ‐ Groups - Erkoç, Temha; Güzel, Erhan (My University, 2009)
A finite group whose complex characters are rationally-valued is called a Q - group. In this paper, Frobenius Q -groups were completely classified.
Keywords: Q-Groups; Frobenius Groups